Using a Cross-Institutional Collaborative Model to Deliver a National Roundtable Conference on Assessment: A Case Study - Brown, N.; Littrich, J. (Journal of University Teaching and Learning Practice, 2008)
This paper describes the organisation, preparation and delivery of a major project, namely, a national roundtable conference on assessment, in the context of a wider project involving the development and application of a model of collaboration between tertiary institutions based on a distributive leadership framework. It analyses feedback received from round table participants and comments on both the utility and the limitations of the adopted model for the purpose of the round table project.